Integrasi Layanan Bimbingan Konseling dan Pendidikan Islam Dalam Upaya Kontrol Diri Siswa SMA - Retno Purwasih; Muhammad Nikman Naser; Ferisa Prasetyaning Utami (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Integration of Counseling Services And Islamic Education In Self-Control Effort Of Senior High School Students Self-control is the ability of individuals to control themselves in behavior, thinking, emotions, and decision making. Self-control can be trained through various approaches, especially counseling guidance and Islamic religious education. The purpose of this study is to determine the level of self-control of high school students and determine the intervention of guidance and counseling services integrated with Islamic religious education. This research is a type of descriptive quantitative research. Data collection was conducted on a sample of 112 people. The results of the self-control measurement score are classified into 5 category levels, namely very high, high, medium, low, and very low. The maximum score of self-control score is 119, the minimum score is 62, the average score is 90.62 and the standard deviation is 12.03. Interventions from the results of measurement and analysis as the basis for a plan for providing guidance and counseling services as well as strengthening student religiosity. The types of services include classical services, group guidance, group counseling, and spiritual guidance.